Hepatic Arterial Infusion Chemotherapy Combined with Lenvatinib and PD-1 Inhibitors for Managing Arterioportal Shunt in Hepatocellular Carcinoma with Portal Vein Tumor Thrombus: A Retrospective Cohort Study - Liu G; Zhu D; He Q; Zhou C; He L; Li Z; Jiang Z; Huang M; Chang B; Wu C (Journal of Hepatocellular Carcinoma, 2024)
Guanxiong Liu,* Duo Zhu,* Quansheng He,* Churen Zhou, Li He, Zhengran Li, Zaibo Jiang, Mingsheng Huang, Boyang Chang, Chun Wu Department of Interventional Radiology, the Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, 510630, People’s Republic of China*These authors contributed equally to this workCorrespondence: Boyang Chang; Chun Wu, Email changby3@mail.sysu.edu.cn; wuch26@mail.sysu.edu.cnPurpose: This study aimed to assess the effectiveness and safety of combining hepatic arterial infusion chemotherapy (HAIC) with lenvatinib (LEN) and PD-1 inhibitors in treating arterioportal shunt (APS) in hepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT).Patients and Methods: Conducted retrospectively, the study enrolled 54 HCC patients with APS and PVTT treated with HAIC, LEN, and PD-1 inhibitors at our center between January 2021 and October 2023. APS improvement, APS recanalization, tumor response, PVTT response rate, overall survival (OS), intrahepatic progression-free survival (InPFS), and adverse events were evaluated.Results: APS improvement was observed in 42 patients (77.8%), with all improvement occurring within two treatment sessions. Complete APS occlusion was achieved in 40 patients (74.1%), and no recanalization occurred. The best objective response rate (ORR) and ORR after two HAIC sessions were 74.1% and 66.7%, respectively. The best PVTT response and PVTT response after two HAIC sessions were 98.1% and 94.4%, respectively. The median OS and InPFS were 10.0 months and 5.0 months, respectively. OS and InPFS were longer in patients with APS occlusion compared to those without (OS 12.1 vs 4.4 months, P< 0.001, InPFS 6.2 vs 2.3 months, P=0.049). ALBI grade, extrahepatic spread, APS disappearance were potential prognostic factors for OS, while APS grade and extrahepatic spread being independently associated with InPFS. No treatment-related mortality occurred.Conclusion: Combining HAIC with LEN and PD-1 inhibitors proves to be both effective and safe in managing APS in HCC with PVTT, potentially improving patient survival.Keywords: hepatocellular carcinoma, shunt, portal vein tumor thrombus, hepatic arterial infusion chemotherapy, combination therapy